Corners, Rooms and Pondoks: a study of informal English learning in three Asian countries - Kellaway, David (2021)
This research explores three informal methods of learning English: English Corner, English Room and Pondok English. The first is common in Mainland China where the label English Corner was coined. English Room is a variant of English Corner encountered in Japan. In the first phase, English Corner and English Room were researched using ethnographic methods, principally participant observation, to investigate the motivations of, and perceived benefits for attendees of learning in these informal environments. The second phase of the study involves action research that built upon the findings of the first phase of the project. The research investigates whether the English Corner and English Room informal learning model could be adapted for use with an audience of parents and schoolchildren in Malaysian Sabah in a subsequent informal learning project that became known as Pondok English. The findings from the study suggest that the model of informal English learning that underpins English Corner, English Room and Pondok English can be adapted, if not directly exported to different contexts and environments. Both adults and children benefit from it: there is evidence of strong instrumental motivation among adults who perceive the link to education and career options available to English speakers. The motivation among children appears more intrinsic and includes the enjoyment of communal singing in English, of being read stories in English, and the opportunity to capture some of their parents’ time in informal and enjoyable short conversations in English that can be replicated at home. The research highlights the importance of literature, libraries, parks and communal mentoring which were essential to ensuring the project’s viability and long term sustainability. The research contributes to knowledge about the value of creating informal, culturally appropriate, cross-generational events and environments to promote the teaching and learning of English as an additional language.